2016
DOI: 10.1074/mcp.m115.054312
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Non-canonical Amino Acid Tagging (QuaNCAT) Proteomics Identifies Distinct Patterns of Protein Synthesis Rapidly Induced by Hypertrophic Agents in Cardiomyocytes, Revealing New Aspects of Metabolic Remodeling

Abstract: Cardiomyocytes undergo growth and remodeling in response to specific pathological or physiological conditions. In the former, myocardial growth is a risk factor for cardiac failure and faster protein synthesis is a major factor driving cardiomyocyte growth. Our goal was to quantify the rapid effects of different pro-hypertrophic stimuli on the synthesis of specific proteins in ARVC and to determine whether such effects are caused by alterations on mRNA abundance or the translation of specific mRNAs. Cardiomyoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 76 publications
1
12
0
Order By: Relevance
“…Pkm2 expression has also been observed in other models of heart disease. In a transverse aortic constriction model, Pkm2 was found to be upregulated in rat hearts (25). Long-term administration of sunitinib, a tyrosine kinase inhibitor used in cancer treatment, also increased expression of Pkm2 and other glycolytic genes, which may indicate a shift toward fetal-like cardiac metabolism (35).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pkm2 expression has also been observed in other models of heart disease. In a transverse aortic constriction model, Pkm2 was found to be upregulated in rat hearts (25). Long-term administration of sunitinib, a tyrosine kinase inhibitor used in cancer treatment, also increased expression of Pkm2 and other glycolytic genes, which may indicate a shift toward fetal-like cardiac metabolism (35).…”
Section: Discussionmentioning
confidence: 99%
“…These changes corresponded with increased HIF1 expression, which bound to a hypoxia response element in the promoter of PKM, indicating a direct link between HIF1 and Pkm2 expression. Increased Pkm2 expression has been noted in other forms of chronic heart disease and has also been associated with heart failure (25,35). It appears that enhanced Pkm2 expression during acute MI is an initial response to injury that is sustained for weeks after injury.…”
Section: Introductionmentioning
confidence: 96%
“…Regulation of their expression is associated with altered blood pressure and heart failure. Other proteomic study reported the regulation of HNRNPA1, HNRNPA2 and ALDOA as a consequence of metabolic remodeling due to cardiac hypertrophic agents [31].…”
Section: Prediction Of Upstream Regulators Associated To Iso-induced Cardiomyocytes Proteome Remodelingmentioning
confidence: 99%
“…At the molecular level, cardiac hypertrophy is characterized by the re-expression of the fetal gene program and an imbalance between protein synthesis and degradation 1-3. As previously shown, prolonged external hypertrophic stimuli markedly activate the process of gene transcription, resulting in excessive protein accumulation in cardiomyocytes and leading to the development of cardiac hypertrophy 4. Pathological hypertrophy has been associated with abnormalities leading to the enhancement of the IGF1-phosphoinositide 3-kinase (PI3K)-Akt pathway, mitogen activated protein kinases (MAPKs), and Gαq signaling.…”
Section: Introductionmentioning
confidence: 97%